The Perspectives of Family Foster Care in the Czech Republic, Hungary, Poland and Slovakia - Herczog, Mária (Public Governance, Administration and Finances Law Review, 2024)
Reforms of the child protection systems, provision of family- and community-based alternative care has been developed to a certain level in all countries in Central and Eastern Europe and has increased the role of care provided by foster families replacing institutions to ensure that the best interests principle is taken into consideration when children are separated from their families. The research describes the foster care system in the so-called Visegrád countries: the Czech Republic, Hungary, Poland and Slovakia, and the results based on at least 50 interviews in each country conducted by local experts on subjective well-being of foster parents, their perceptions about their roles and place in their respective countries and their needs. The article includes the legal framework, recruitment, preparation and support to foster families, their subjective well-being and needs in the four countries, including the history of their child protection systems to better understand the current situation. The outcomes show differences in approach to foster care, the perception on the roles, responsibilities and needs based on the different traditions, earlier and current policies and practices. Understanding the attitude changes related to the rights of children, those in vulnerable situations, and to their families of origin would be essential to further develop and improve the child welfare and protection systems, and listening to children on their perceptions and the realisation of their rights.